Linear regression model for assessing the yield loss of mustard due to Alternaria leaf blight disease - SRIKANTA DAS, SUNITA MAHAPATRA*and (Indian Phytopathology, 2016)
Measurement of yield loss of mustard through the correlation between seed yield, 1000 seed weight vs. disease severity and avoidable yield loss of seed yield and 1000 seed weight vs. disease severity using linear regression analysis models for two consecutive years showed that the attainable yield of mustard were 1944 kg to 1980 kg ha-1 and drop of 12.65 kg to 12.83 kg ha-1 due to every one percent unit increase in disease severity. Similarly attainable 1000 seed weight were 4.30 g to 4.34 g for both the years and a drop of 0.03 g for every one percent unit increase in disease severity. In case of avoidable yield loss and 1000 seed weight, 38.90% to 41.19% seed yield loss and 37.04% to 37.17% 1000 seed weight could be avoided with every one percent decrease in disease severity. The pooled mean equation of all the characters were y = 1963-12.78 X for seed yield, y = 4.327-0.028 X for 1000 seed weight, y = 40.10-0.682 X for avoidable seed yield loss, y = 37.17-0.71 X for avoidable 1000 seed weight which were confirmed by high co-efficient of determination (R2) above 96 to 97%.